PEMODELAN TINGKAT PENGANGGURAN TERBUKA TERHADAP FAKTOR – FAKTOR YANG MEMPENGARUHINYA DI PULAU KALIMANTAN MENGGUNAKAN REGRESI NONPARAMETRIK SPLINE TRUNCATED - Ma’rifa, Aulia; Anggraini, Dewi; Annisa, Selvi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2024)
The Open Unemployment Rate is an indicator used to measure the unemployment rate in the labor force. Kalimantan Island is one of the largest islands in Indonesia with a population of around 16.8 million people and is still experiencing problems in overcoming unemployment. Efforts are needed to overcome the problem of unemployment so that it can be resolved and does not have an impact on many things. The purpose of this study was to determine the factors that influence unemployment in Kalimantan using truncated spline nonparametric regression. The nonparametric spline truncated regression analysis approach is used because the pattern of relationship between the open unemployment rate and the factors that are thought to influence it does not form a specific pattern. The results of this study obtained the best model using one knot, with the average length of schooling and labor force participation rate variables able to explain the variability of the open unemployment rate in Kalimantan of 56,05 percent.